ANTECEDENTS DARI CUSTOMER RETENTION PADA NASABAH BANK BNI 46 TRISAKTI GROGOL HARMONI - Banned, Meikol (JURNAL ILMIAH M-PROGRESS, 2023)
The purpose of this study is more focused on customer retention. Determine the effect of customer retention is important for companies to future progress. for customer retention seems to result from tlte kind repeated decisions by  the  customer. In this  study the authors investigated the effects of locational convenience, One stop shopping convenience, Satisfaction, Trust, Commitment, Firm expertise, Firm  reputation on  customer  retention  in  PT Bank  Negara  Indonesia  (Persero) Tbk Trisakti University branch. Design data used in this study is the multiple regression using SPSS version 15.Research methods used in this study is to collect data through questionnaires to 150 customers of PT BNI Trisakti Grogol in West Jakarta Branch consisting of Lecturers, Students, Employees, and the general public as a customer to seek feedback on the questionnaire design.Results of research can be conclude that there was a significant  positive  effect  on commitment to the beta value of 0.281 and firm reputation with a beta value of 0.328. Implications - This research provides evidence  that  the  commitment  and  firm  reputation of the company should get serious attention  and  consideration  for management,  maintain and enhance the company’s commitment and reputation is important  so  that  customers remain loyal. Reputation and commitment directly affect how customers respond to failure. Keywords:  Locational convenience, One stop shopping  convenience,  Satisfaction, Trust, Commitment,Firm expertise, Firm reputation and Customer retention.